The asymptotic aggregation problem and the macrodescription of high dimensional systems - Adilov, G. R.; Tinaztepe, G. (Mathematical Modelling and Analysis, 2005)
In this paper, the aggregation problem for high dimensional systems is studied in a different point of view. The deviations occuring when macro‐descriptions are built and evaluated statistically. The systems asymptotic ideal with the aggregation is studied in this sense. Also for some classes of matrices the leading eigenvalues and norms have been taken as aggregate and aggregation is studied in this sense (errors are evaluated statistically).Asimptotinis agregacijos uždavinys ir didėlės eilės eilės sistemų makrodeskripcijaStraipsnyje nagrinėjamas daugiamačių sistemų agregacijos uždavinys. Nuokrypiai, atsirandantys keičiant sistemą jos makrodeskripcija, įvertinti statistiškai. Sistemos agreguotasis asimptotinis idealas nagrinėjamas tuo pačiu požiūriu. Taip pat straipsnyje nagrinėjama kelių matricų klasių agregacija, ju pagrindines tikrines vertes ir normas naudojant kaip agregatą ir nuokrypius įvertinant statistiškai.First Published Online: 14 Oct 2010